2019
DOI: 10.3390/medsci7070078
|View full text |Cite
|
Sign up to set email alerts
|

Steroid Mass Spectrometry for the Diagnosis of PCOS

Abstract: The most appropriate steroids to measure for the diagnosis of hyperandrogenism in polycystic ovary syndrome (PCOS) are still open to debate but should preferably be measured using a high-quality method such as liquid chromatography tandem mass spectrometry (LC-MS/MS). Measurement of testosterone is recommended in all of the current clinical guidelines but other steroids, such as androstenedione and dehydroepiandrosterone sulfate (DHEAS), have also been shown to be useful in diagnosing PCOS and may give additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 48 publications
1
17
0
Order By: Relevance
“…In our study, we found that fT concentrations correlated with metabolically adverse parameters (BMI, HOMA-index, and HbA1c), whereas there was no correlation between A and metabolic aspects. This is in contrast with the findings of O’Reilly et al that described a significant association between high A concentrations and an adverse metabolic phenotype, but confirms the results in the metanalyses by Amiri et al [ 11 , 12 , 13 , 14 , 15 ].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In our study, we found that fT concentrations correlated with metabolically adverse parameters (BMI, HOMA-index, and HbA1c), whereas there was no correlation between A and metabolic aspects. This is in contrast with the findings of O’Reilly et al that described a significant association between high A concentrations and an adverse metabolic phenotype, but confirms the results in the metanalyses by Amiri et al [ 11 , 12 , 13 , 14 , 15 ].…”
Section: Discussionsupporting
confidence: 86%
“…Moreover, some authors argue that a multi-steroid profile could be more sensitive in detecting hyperandrogenism in these patients [ 10 , 11 , 12 ]. It is likely that the use of liquid chromatography in tandem with mass spectrometry (LC-MS/MS), the gold standard for steroids measurements, allowing simultaneous measurement of several androgens, may improve the diagnosis and phenotyping of PCOS patients [ 13 ]. However, this technique has had limited application in clinical practice because of its complexity, and its difficulty in preparing quality control samples, which increased with the number of analytes.…”
Section: Introductionmentioning
confidence: 99%
“…14 Many studies have confirmed that the LC-MS/MS had good performance in the determination of T, DHEAS, A4 or other steroids, [16][17][18] offering an ideal alternative methodology in the determination of hyperandrogenism in PCOS. 19 Some previous studies have shown that the simultaneous determination of T and A4, or T and DHT was achievable with excellent accuracy and little matrix interference. 20,21 As part of the continual efforts to improve the laboratory diagnostic accuracy of hyperandrogenism in PCOS patients, we established an efficient LC-MS/MS method for simultaneous measurement of serum T, A4, DHEAS, DHT, and 17-OHP and evaluated the clinical utility of this androgen testing panel with the PCOS patients.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the diagnosis, prognosis, and management of such diseases strongly depend on accurate quantification of steroid hormones in biological fluids. Imbalances in production or metabolism of steroids lead to a wide range of steroid related disorders, sometimes complex adrenal diseases, including congenital adrenal hyperplasia (CAH) [ 71 , 72 , 73 , 74 , 82 , 83 ], adrenal cancer [ 4 , 6 , 7 , 45 , 75 , 76 ], hyperaldosteronism [ 45 , 84 , 85 , 86 , 87 ], Cushing’s syndrome [ 68 ], disorder of sexual development (DSD) [ 44 ], and polycystic ovary syndrome (PCOS) [ 44 , 69 , 88 ]. For some of these disorders, it is still open to debate on which steroids are most appropriate to be quantified for the related diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…About five decades ago, Gower et al described alterations in steroid hormones production as possible markers of malignancy in adrenal tumors [64,65]. Subsequently, the application of steroid profiling in the diagnosis of adrenocortical disorders has been described on many occasions: firstly, by using difficult chromatographic separations and colorimetric or immunoassay procedures [66,67], more recently replaced by targeted metabolomics techniques using GC-MS and LC-MS/MS, respectively [4,[68][69][70][71][72][73][74]. Even if not enough data on steroid profiling have been reported to be able to define a distinct malignant steroid fingerprint for ACC, biochemical evidence showed how most ACCs are characterized by accumulation of steroid precursor metabolites rather than by end products of steroidogenesis [75].…”
Section: Steroid Profiling As a Diagnostic Tool In Adrenocortical Carmentioning
confidence: 99%